2016
DOI: 10.1039/c6ob02038k
|View full text |Cite
|
Sign up to set email alerts
|

A novel coelenterate luciferin-based luminescent probe for selective and sensitive detection of thiophenols

Abstract: The first dual bioluminescent and chemiluminescent sensor for detecting highly toxic thiophenols has been developed. Such a probe was designed by using a coelenterazine analogue as the luminophore and dinitrophenyl ether as the recognition moiety. It should be noted that this probe displayed good sensitivity and selectivity toward thiophenols, and has been effectively applied for the quantitative detection of thiophenols in aqueous media and complex biological samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…The reported caged-CTZ probes usually have the C-3 carbonyl of coelenterazine caged by the analyte of interest. Such probes have been reported to measure b-galactosidase activity, 257 for the detection of thiophenols, 258 and for the targeting and detection of biothiols such as cysteine, glutathione and homocysteine. 259 A number of caged-CTZ probes were also included as glycosidase inhibitors in a patent by the Promega corporation.…”
Section: Sensing Of Ph Metal Ions Reactive Oxygen Species (Ros) Enmentioning
confidence: 99%
“…The reported caged-CTZ probes usually have the C-3 carbonyl of coelenterazine caged by the analyte of interest. Such probes have been reported to measure b-galactosidase activity, 257 for the detection of thiophenols, 258 and for the targeting and detection of biothiols such as cysteine, glutathione and homocysteine. 259 A number of caged-CTZ probes were also included as glycosidase inhibitors in a patent by the Promega corporation.…”
Section: Sensing Of Ph Metal Ions Reactive Oxygen Species (Ros) Enmentioning
confidence: 99%
“…Chemiluminescence- and bioluminescence-based analytical assays have a number of advantages including simple procedures and equipment as no excitation light is needed, low background signal and high sensitivity, and good biocompatibility [132,133]. Li et al reported a dual bioluminescent and chemiluminescent PhSH probe ( 56 ) (Figure 23) based on coelenterazine [134]. In Tris-HCl buffer (50 mM, pH 7.4) with the addition of luciferase, the probe system can be used for bioluminescent sensing of PhSH with an emission peak at 445 nm.…”
Section: Probes Based On the Recognition Unit Of 24-dinitrophenylmentioning
confidence: 99%
“…The firefly luciferase system is widely used for BLI systems, which generally employ LH 2 or aminoluciferin as a substrate in the presence of ATP, Mg 2+ , and O 2 to produce detectable photons. Based on this strategy, several bioluminescent probes have been applied to the in vivo imaging of H 2 S, F − , H 2 O 2 , nitroreductase, aminopeptidase, and so on [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%